1997
DOI: 10.1111/j.1399-6576.1997.tb04769.x
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of the prone position on the incidence of barotrauma in oleic acid‐induced lung injury under continuous positive pressure ventilation

Abstract: It was concluded that in lung injury dogs, the prone position has beneficial effects on the incidence of ventilator-induced barotrauma and arterial oxygenation when compared with the lateral position. Ventilator-induced barotrauma may occur at lower airway pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
1
7
0
1
Order By: Relevance
“…Moreover, while the injury in the supine position was distributed mainly to the dependent lung regions, where collapsing and reinflating phenomena are more likely to occur, in the prone position lung injury was not only reduced in total, but was more homogeneously distributed. Similar findings were obtained by other authors [33] who observed a lower incidence of pneumothorax in dogs kept prone. In conclusion, prone positioning can exert a protective effect on the mechanically ventilated injured lung.…”
Section: Ventilator-associated Lung Injury and The Prone Positionsupporting
confidence: 92%
“…Moreover, while the injury in the supine position was distributed mainly to the dependent lung regions, where collapsing and reinflating phenomena are more likely to occur, in the prone position lung injury was not only reduced in total, but was more homogeneously distributed. Similar findings were obtained by other authors [33] who observed a lower incidence of pneumothorax in dogs kept prone. In conclusion, prone positioning can exert a protective effect on the mechanically ventilated injured lung.…”
Section: Ventilator-associated Lung Injury and The Prone Positionsupporting
confidence: 92%
“…Positional studies in animal models of lung injury also showed benefits to prone positioning (144,341,530). In dogs undergoing oleic acid injury, more uniform distribution of perfusion was noted in the prone position before injury and redistribution of perfusion away from dependent regions in prone but not supine position following injury (693).…”
Section: Effects Of Posture On Hemodynamicsmentioning
confidence: 96%
“…The effect of body position on oxygenation and pulmonary oxygen uptake has been studied in human medicine with the current evidence suggesting that oxygenation and pulmonary oxygen uptake improve when a patient is moved from dorsal recumbency (supine position) to sternal recumbency (prone position) 1–3 . Experimental studies in sheep, pigs, and dogs have shown a significantly higher PaO 2 when patients are in sternal recumbency as compared with dorsal recumbency 4–14 . A suggested mechanism for this change is a reduction in ventilation:perfusion mismatch and therefore an improvement in pulmonary oxygen uptake 4–14 .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies in sheep, pigs, and dogs have shown a significantly higher PaO 2 when patients are in sternal recumbency as compared with dorsal recumbency 4–14 . A suggested mechanism for this change is a reduction in ventilation:perfusion mismatch and therefore an improvement in pulmonary oxygen uptake 4–14 . The relevance of these studies to spontaneously breathing, conscious canine clinical patients is uncertain.…”
Section: Introductionmentioning
confidence: 99%